ANALISIS KEPUTUSAN PEMILIHAN SISWA EKSTRAKURIKULER TERBAIK DENGAN MENGGUNAKAN METODE GRAY ABSOLUTE DECISION ANALYSIS - Wahyu Nur Alimyaningtias; Riski Zulkarnain; Syaddam Syaddam; Lisda Hani Gustina; Gray Hansen Limantoro (Jurnal Data Mining dan Sistem Informasi, 2024)
School extracurriculars are non-formal learning within formal education as a forum for students to be able to express their knowledge and skills in a particular field. Immortal itself is one of the photography extracurriculars located at Vocational High School 3 Balikpapan and has been established since 2014. The Immortal extracurricular initially did not have a category for the best students, so, if it was required to categorize it, the method used would be less efficient. So, the GADA method is used to find the best students from the Immortal extracurricular. The GADA method will address problems associated with incomplete or uncertain information, which are often encountered in real-world situations. This research makes a significant contribution to the development of decision-making systems in the educational environment, especially in the management of extracurricular activities.